2020
DOI: 10.1166/jctn.2020.8777
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Consumers’ Attitude Towards Mobile Payment Feasibility

Abstract: This study discussed about the impact of consumers’ attitude towards mobile payment feasibility in Malaysia. The research focused on three research objectives which are; (1) to identify the consumers’ concerns that influencing the mobile payments feasibility in Malaysia, (2) to investigate the relationships between perceived security, payment culture, perceived usefulness and perceived ease of use, and (3) to identify the main consumers’ concern that influencing the mobile payment feasibility in Malaysia. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A systematic literature review from 2018 to 2021 on this subject area revealed that there were 119 articles published in academic journals listed on the SCOPUS database, 3 with 2019 and 2020 as the years with the most prolific number of publications (45%). Of these, about 60% (64 of the 119) were based on technology acceptance models, such as the Technology Acceptance Model (TAM), the Theory of Planned Behavior (TPB), the Unified Theory of Technology Acceptance and Use (UTAUT) for Unified Theory of Acceptance and Use of Technology) (Abdul Aziz et al 2020;Nur and Panggabean 2021;Malek et al 2017;Flavian et al 2020;Hee et al 2020;Liébana-Cabanillas et al 2018;Patil et al 2020;Wong et al 2021) -all of which were derived from the Theory of Reasoned Action (TRA) (Ajzen and Fishbein 1973;Fishbein and Ajzen 1975). Another 15% analyzed the use of applications for mobile payment from a perspective of various enablers or barriers (Cheng et al 2019;Zhang, Luximon, and Song 2019 In addition, nearly all were quantitative in nature, with the exception of Moghavvemi et al (2021), who used in-depth interviews to understand acceptance of mobile payments of merchants.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…A systematic literature review from 2018 to 2021 on this subject area revealed that there were 119 articles published in academic journals listed on the SCOPUS database, 3 with 2019 and 2020 as the years with the most prolific number of publications (45%). Of these, about 60% (64 of the 119) were based on technology acceptance models, such as the Technology Acceptance Model (TAM), the Theory of Planned Behavior (TPB), the Unified Theory of Technology Acceptance and Use (UTAUT) for Unified Theory of Acceptance and Use of Technology) (Abdul Aziz et al 2020;Nur and Panggabean 2021;Malek et al 2017;Flavian et al 2020;Hee et al 2020;Liébana-Cabanillas et al 2018;Patil et al 2020;Wong et al 2021) -all of which were derived from the Theory of Reasoned Action (TRA) (Ajzen and Fishbein 1973;Fishbein and Ajzen 1975). Another 15% analyzed the use of applications for mobile payment from a perspective of various enablers or barriers (Cheng et al 2019;Zhang, Luximon, and Song 2019 In addition, nearly all were quantitative in nature, with the exception of Moghavvemi et al (2021), who used in-depth interviews to understand acceptance of mobile payments of merchants.…”
Section: Theoretical Frameworkmentioning
confidence: 99%